2012
DOI: 10.1363/3807812
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Empowerment and Ideal Family Size: An Examination of DHS Empowerment Measures in Sub-Saharan Africa

Abstract: The literature on women's empowerment has defined and conceptualized "empowerment" using different and often interchangeable terms, including "autonomy," "status" and "agency." 1,2 According to one definition, empowerment is "the expansion of people's ability to make strategic life choices in a context where this ability was previously denied to them." 3 Two central components of empowerment are the agency and the resources needed to exercise life choices. 2,3 In addition, the construct of women's empowerment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
167
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(189 citation statements)
references
References 45 publications
12
167
2
8
Order By: Relevance
“…This suggests that a woman's reproductive schedule may reflect her spouse's preferences more than her own. Finally, some direct metrics of female autonomy and indirect measures, such as education, have been implicated as important predictors of fertility decline or lower desired fertility [30,31]. This has led some researchers to suggest that the nineteenth to twentieth century demographic transitions reflect female preferences for lower fertility [3,4], and furthermore that these preferences may reflect females' adaptive reproductive strategies for smaller family sizes [20,32 -35].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a woman's reproductive schedule may reflect her spouse's preferences more than her own. Finally, some direct metrics of female autonomy and indirect measures, such as education, have been implicated as important predictors of fertility decline or lower desired fertility [30,31]. This has led some researchers to suggest that the nineteenth to twentieth century demographic transitions reflect female preferences for lower fertility [3,4], and furthermore that these preferences may reflect females' adaptive reproductive strategies for smaller family sizes [20,32 -35].…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 On the basis of different literatures, women's empowerment should be associated with a smaller ideal number of children in many African countries. 6 Studies conducted in African countries (Nigeria, Guinea, Zambia and Mali) indicated that women's status and empowerment are important factors for controlling and reducing women's fertility through two main pathways: (1) desire to reduce family size and (2) ability of women to satisfy their desire for an ideal family size through the use of family planning methods. As a woman becomes more empowered to negotiate fertility decision making, they have more control over contraceptive use to achieve their desire.…”
Section: Introductionmentioning
confidence: 99%
“…Much past literature has explored the many dimensions that can be measured to understand empowerment, including concepts such as power, autonomy, status, agency, mobility, decision-making power, etc. (Hindin 2000;Roushdy 2004;Upadhyay and Karasek 2012).…”
Section: Figurementioning
confidence: 99%
“…First, to measure dimensions of empowerment related to social/cultural norms, we use a series of questions from the Demographic and Health Surveys revolving around acceptability of wife beating, inequality in relationships, gender preferences, etc., as have been used by numerous scholars to measure women's empowerment (Linos, Khawaja, and Al-Nsour 2010;Upadhyay and Karasek 2012). Second, we use questions about couples' relationship quality, including partner communication, and marital relationship quality, to address another dimension of empowerment related to couples' dynamics and decision-making.…”
Section: Figurementioning
confidence: 99%